Legal Responsibility of Companies That are Negligent in Managing Waste Which Causes Environmental Damage - Gandhi Pharmacista (Fox Justi : Jurnal Ilmu Hukum, 2024)
The increasing number of companies in Indonesia will have an impact on economic growth and job creation in Indonesia. However, along with this growth, companies, especially in the industrial sector, will also produce waste as a result of the production process. There are still many companies that still neglect to manage their waste, which can cause damage to the surrounding environment. This research aims to analyze the legal responsibility of companies that are negligent in waste management, causing environmental damage. This research uses a normative legal approach. The results of this research reveal that based on the Environmental Protection Law, environmental crimes are defined as crimes, with corporate legal responsibility divided into three types, namely according to civil, criminal and administrative law. In a civil context, companies must pay compensation due to the environmental impacts they cause. Article 87 stipulates that those responsible for businesses and/or activities that violate environmental law are obliged to pay compensation. Articles 116 to 118 state that environmental crimes involve business entities and individuals who can be subject to criminal sanctions. In addition, the Law also regulates administrative sanctions, such as fines or suspension of permits, to ensure compliance with environmental provisions. Overall, this Law provides a strong foundation for corporate legal accountability, involving civil, criminal and administrative aspects.